2013
DOI: 10.1111/josh.12036
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Providing the Sexuality Education That Teachers Believe Students Need

Abstract: Addressing teachers' barriers requires a multipronged approach, including curriculum development and evaluation, training, and reframing the policy debate to support a wider range of sexuality education topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 18 publications
2
59
2
Order By: Relevance
“…A previous study reported that parental responses were a perceived area of concern when teaching sexual education through a traditional curriculum, 21 whereas our study demonstrated that our parent/guardian stakeholders strongly supported the videogame intervention and found the game to be valuable in teaching their children about the topics of sex, alcohol, and drugs. Additionally, site coordinators and community partners embraced the use of technology in their respective settings, viewing it as a beneficial tool.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…A previous study reported that parental responses were a perceived area of concern when teaching sexual education through a traditional curriculum, 21 whereas our study demonstrated that our parent/guardian stakeholders strongly supported the videogame intervention and found the game to be valuable in teaching their children about the topics of sex, alcohol, and drugs. Additionally, site coordinators and community partners embraced the use of technology in their respective settings, viewing it as a beneficial tool.…”
Section: Discussioncontrasting
confidence: 42%
“…As in previous studies, 14,15,21 after-school/ school coordinators who were interviewed for this project identified the need of cost consideration for this type of intervention, reflecting the essential nature of this component in any full-scale intervention implementation and dissemination. Programs have limited budgets, and for successful implementation, those that directly influence the budgets must recognize the cost-benefit of the initial monetary investment and potential learning outcomes for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…we found only one study that explored the support or policies adopted by intermediate structures, such as regional education departments, although the results refer to the odds of teachers providing SE 13 . indeed, there is a predominance of studies that examine either the predictors of teachers delivering SE, rather than implementation encompassing the whole school, or the barriers to SE implementation [13][14][15] . Facilitating factors have received little research attention.…”
Section: Implementation Of School-based Se Within An Ecological Framementioning
confidence: 98%
“…At the microsystem level, first consideration is made for features of the school, such as whether it is a state school 12,15 or a school with a tradition of making SE an important part of the curriculum, rather than forgoing it in favour of meeting other academic goals 9,14,16 . Second, the cultural environment is important and, more specifically, the non-existence of sexual conservatism and restrictive religious beliefs is essential 14,16 .…”
Section: Implementation Of School-based Se Within An Ecological Framementioning
confidence: 99%
“…Research has shown that teachers of even theoretically comprehensive sexuality education curricula often face barriers in teaching about more controversial topics such as abortion and sexual orientation and are forced to stint on coverage of such subject matter (Eisenberg, Madsen, Oliphant, & Sieving, 2013;Shindel & Parish, 2013). This is primarily due to political and administrative objections, or concerns about parental objections, to "controversial" topics being discussed in the classroom (Dailard, 2001;Wilson, 2000).…”
mentioning
confidence: 97%